Anaphylactic Shock in Patient with Hepatic Hydatic Cyst: An Experience at a Rural Hospital - Khapung, Robin; Mahaset, N. (Journal of Karnali Academy of Health Sciences, 2018)
Hydatid disease is mainly caused by infection with the larval stage of the dog tapeworm Echinococcus granulosus. Infestation by hydatid disease in humans most commonly occurs in the liver (55- 70%) followed by the lung (18- 35%); the two organs can be affected simultaneously in about 5-13% of cases. Hydatid disease is endemic in many parts of the world, including India, Africa, South America, New Zealand, Australia, Turkey and Southern Europe. Hydatid disease is more prevalent in rural areas where there is a closer contact between people and dogs and various domestic animals which act as intermediate vectors. Hydatid disease remains frequent in JUMLA. In Karnali Academy of Health sciences 26 surgeries for hydatid cyst was done between 2016-2018. Hydatid cyst of liver in a child is a challenge to anesthesiologist in a remote city such as Jumla. Anaphylactic and anaphylactoid reactions during anesthesia are a major cause of concern for anesthesiologists. During the perioperative period, any symptomatology relating to sudden onset hemodynamic collapse or increased airway pressures during certain surgical procedures should raise suspicion of anaphylaxis. We report a case of intraoperative sudden anaphylaxis and its management.